1991
DOI: 10.1161/01.str.22.8.1010
|View full text |Cite
|
Sign up to set email alerts
|

Microinfarction in classic migraine? A study with magnetic resonance imaging findings.

Abstract: By means of magnetic resonance imaging we investigated a total of 45 patients suffering from classic migraine; 25 patients had been treated in our department for classic migraine over the past 2 years (group A), and 20 other patients investigated between 1976 and 1984 were reexamined for this study (group B). Thirty-two age-and roughly sex-matched healthy volunteers underwent magnetic resonance imaging and served as controls (group C). There was a trend for patients with classic migraine to have more subcortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
1
18
1
1
Order By: Relevance
“…Although WMF represent the most common finding identified by MRI in migraine patients, great variability has been reported (1)(2)(3)(4)(5)(6)(7)(8). Differences in screening criteria, such as sample size, age, MRI methodology and data interpretation for patients and controls, may combine to explain this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Although WMF represent the most common finding identified by MRI in migraine patients, great variability has been reported (1)(2)(3)(4)(5)(6)(7)(8). Differences in screening criteria, such as sample size, age, MRI methodology and data interpretation for patients and controls, may combine to explain this variability.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 59% of controls (aged 35–60 years) had a least 1 small (3 mm diameter) WML. Note the discrepancy with data from the earlier MRI studies, in which percentages of WMLs in controls ranged from “only” 2–20% 27,68 . Higher sensitivity (and also specificity) can be the result of thinner slices, reduced or absent interslice gap, and the use of more sensitive and more specific MR sequences, like FLAIR 59,74 .…”
Section: White Matter Lesionsmentioning
confidence: 60%
“…From the moment MRI became available for the evaluation of the brains of migraine patients, reports exist on the presence of white matter hyperintense signal abnormalities on T 2 ‐weighted MRI sequences in these cases 66,67 . Numerous studies have reported on WMLs in migraine patients but results are conflicting 25–29,68–73 . Some only reported prevalence of WMLs in migraine patients, without the use of a control group; 71–73 most reported an increased prevalence in migraine patients compared to controls, 25–29 and a few did not find a statistically significant difference 68–70 .…”
Section: White Matter Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…T 2 -weighted MR imaging has been utilized in a number of other conditions including, for example, head injury (Yanagawa et al, 2000;Wardlaw and Statham, 2000;Hadley et al, 1988;Gentry et al, 1988), cerebral infections Thurnher et al, 1997), migraine (Ferbert et al, 1991;Soges et al, 1988), psychiatric disorders (Buckley et al, 1995) and alcohol-related diseases (Sullivan and Hefferbaum, 2001;Park et al, 2001). The majority relied on only qualitative assessment; however, where quantitation was performed, increased sensitivity was demonstrated.…”
Section: Other Conditionsmentioning
confidence: 99%